Copper and zinc removal from contaminated soils through soil washing process using ethylenediaminedisuccinic acid as a chelating agent: A modeling investigation. Issue 3 (September 2016) - Race, Marco; Marotta, Raffaele; Fabbricino, Massimiliano; Pirozzi, Francesco; Andreozzi, Roberto; Cortese, Luciano; Giudicianni, Paola
Highlights: Soil washing by EDDS markedly reduced copper and zinc concentration in polluted soils. The soil washing process is particle diffusion controlled. A simplified approach is proposed to study the diffusion process metal/EDDS complexes. Estimation of diffusion coefficients for Cu/EDDS and Zn/EDDS complexes. Abstract: This study demonstrated that soil washing using ethylenediaminedisuccinic acid (EDDS) as a chelating agent was efficient at removing copper and zinc from real polluted soils. Only the exchangeable and reducible fractions of Cu and Zn were extracted by EDDS. Intra-particle diffusion was the main rate controlling step in this extraction of heavy metals from the solid matrix. Different contributions were found by applying the Weber and Morris intraparticle diffusion model resulting from the different roles of superficial and intra-particle diffusive processes.The diffusion coefficients of the Cu/EDDS and Zn/EDDS complexes in real contaminated soils were estimated using simplified diffusive models (based on Crank's and Vermeulen's approximations). The relationship between the grain size and diffusion coefficient was also evaluated. In particular, the intraparticle diffusion coefficients increased with increasing the particle size, thus indicating that the smallest granulometric fractions are characterized by a higher percentage of micropores than the largest fractions.